PEMBUATAN PETA DIGITAL DESA WONOHARJO BERBASIS QR CODE “DIGITAL MAP WONOHARJO VILLAGE BASED ON QR CODE” - Widijanto, Hery; Danu Prihanto, Hendrawan; Ainun Syah Alfarizi, Ilham; Naufal Ramadhan, Muhammad (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Wonoharjo Village is located in Nguntoronadi District, Wonogiri Regency ,Central Java, which has alot of potential in agriculture and water .Wonoharjo Village does not yet have a digital map, characteristic of a developed village. In this activity ,KKN students carried out the activity